Effects of Donepezil and Medroxyprogesterone Versus Placebo on Weaning in Adult Patients With Non-Pulmonary Etiologies Receiving Invasive Mechanical Ventilation: A triple‐blind Randomized Clinical Trial - Alizadeh, Zahra; Sahebnasagh, Adeleh; Hadadzadegan, Navid; Mohammadi, Farhad; Saghafi, Fatemeh (Frontiers in Pharmacology, 2021)
Medroxyprogesterone and donepezil could be used as respiratory stimulants in ventilated patients. However, no randomized placebo-controlled trial is available to confirm this approach and compare these drugs. The aim of the current study was to evaluate the effects of donepezil or medroxyprogesterone compared to the placebo in improvement in respiratory status and weaning facilitation in critically ill adult patients receiving mechanical ventilation. This randomized, triple-blind trial was conducted on 78 ventilated patients in intensive care units (ICU). Patients who were intubated due to pulmonary disorders were ruled out. Patients were randomized in a 1:1:1 ratio to receive 5 milligram (mg) donepezil (n =23) or 5 mg medroxyprogesterone (n = 26), or placebo (n = 24) twice a day until weaning (maximum 10 days). The primary endpoints were weaning duration and duration of invasive mechanical ventilation. Secondary endpoints included rate of successful weaning, changes in arterial blood gas (ABG) parameters, GCS and sequential organ failure assessment (SOFA) score, hemoglobin (Hgb), ICU-mortality, and duration of ICU stay, were measured before and after the intervention and if successful weaning was recorded. Of 78 studied patients who were randomized, 59 were weaned successfully. 87% patients in donepezil and 88.5% patients in medroxyprogesterone groups were successfully weaned compared to 66.7% patients in the placebo group. However, this difference was not statistically significant (P-Value=0.111). Changes in pH, mean duration of intubation, and weaning duration was statistically different in donepezil compared with the control group (P-value Value < 0.05). No significant difference in ABG, Hgb, GCS, and SOFA score, and duration of intubation was seen in the medroxyprogesterone group, but weaning duration was significantly reduced to 1.429 days compared with the control group (P-Value =0.038) The results of this clinical trial have demonstrated that the administered dose of medroxyprogesterone and donepezil can expedite the weaning process by reducing the weaning duration compared to placebo. Furthermore, the total duration of invasive ventilation was significantly lower in the donepezil group compared to the control group. Future clinical trials with a larger sample size will determine the exact role of medroxyprogesterone and donepezil in mechanically ventilated patients